Penerapan Sistem Informasi Tagihan (SiTagih) untuk Meningkatkan Kinerja Pencatatan Tagihan dan Keuangan - Faisol, Ahmad; Ashari, Mochammad Ibrahim; Orisa, Mira (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2020)
PT Semesta Mitra Sejahtera is a company engaged in the field of public goods transportation services. The existing system is still manual, especially for recording bills, determining the allocation of goods in trucks, and making Bill Notes. To increase efficiency and effectiveness, a new computerized system is needed to accelerate the administration and billing processes that are accurate to the users of transportation services according to the needs of the company owner. The database used is Microsoft Access, while the application is created using the Visual Basic .NET programming language. The results achieved in the form of computer applications that are easy to operate because of its user-friendly appearance. After the application is complete, the service team conducts training for users at PT Semesta Mitra Sejahtera. This training is expected to help partners in mastering the use of applications, especially for recording bills.Â How to cite:Faisol, A., Ashari, M. I., Orisa, M. (2020). Penerapan Sistem Informasi Tagihan (SiTagih) untuk Meningkatkan Kinerja Pencatatan Tagihan dan Keuangan. Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 5(1), 38-46.DOI: https://doi.org/10.26905/abdimas.v5i1.3564 Â